2019
DOI: 10.1186/s12936-019-2760-8
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of malaria in an endemic area of Indonesia

Abstract: Background Malaria is an increasing concern in Indonesia. Socio-demographic factors were found to strongly influence malaria prevalence. This research aimed to explore the associations between socio-demographic factors and malaria prevalence in Indonesia. Methods The study used a cross-sectional design and analysed relationships among the explanatory variables of malaria prevalence in five endemic provinces using multivariable logistic regression. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 41 publications
6
31
1
5
Order By: Relevance
“…Inconsistent with our finding, sociodemographic factors, use of mosquito nets and unimproved conditions of housing structure were associated with higher malaria prevalence. 21 About 79.3% of the study participants were aware of the fact that Plasmodium is the cause of death in malaria endemic areas. Of the 271 parents/caregivers, 71.2% knew about the mode of malaria transmission via mosquitoes' bite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent with our finding, sociodemographic factors, use of mosquito nets and unimproved conditions of housing structure were associated with higher malaria prevalence. 21 About 79.3% of the study participants were aware of the fact that Plasmodium is the cause of death in malaria endemic areas. Of the 271 parents/caregivers, 71.2% knew about the mode of malaria transmission via mosquitoes' bite.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, another study also showed that individuals who did not use mosquito nets at night were more likely to have malaria than those who did. 21 A two-year prospective cohort study done at Arba Minch Zuria district, Ethiopia showed that the ITNs use fraction reached 69%, but the utilization in under 5 year old children it was very low. 28 Similarly, there was high percentage (93.3%) access for ITN by parents'/caregivers, still it is not considerably applied for under 5 year old children.…”
Section: Discussionmentioning
confidence: 99%
“…In Mali, in particular, the disease remains highly endemic with resurgence in epidemic prone areas [ 4 ]. Many recent studies have shown multiple factors influencing malaria transmission, including socio-economics, demographic and climatic conditions [ 38 , 39 , 40 , 41 ] as well as behaviors and access to health care [ 42 ]. Environmental, meteorological, vegetation and hydraulic components have been identified to play an important role in malaria transmission dynamics [ 7 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For a household background variables, we considered those commonly investigated in the malaria literature (e.g. see [26,16,27,17,28,29]) and these include number of household members, whether household had mosquito nests that can be used while sleeping or not which was a dichotomous variable with the categories yes or no; whether household sprayed interior walls of the dwelling against mosquitoes within the last 12 months prior to the survey or not which was a dichotomous variable with the categories yes or no; number of rooms in the dwelling, the dwelling has windows which was a dichotomous variable with categories yes and no; main source of drinking water which was a three-category variable with the categories unprotected, protected source and piped water; main material of the house wall which was a three-category variable with the categories no wall, wood and finished wall (e.g. bricks); main material of house floor which was a three-category variable with the categories earth plastered by dung, rudimentary and finished floor (e.g.…”
Section: Outcome and Explanatory Variablesmentioning
confidence: 99%